Simplify the porder using the Distributiva Propariy \[ (3)-1)(6+5) \] \[ (3 x-1)(3+3)= \] \( \square \) (Simplify your answer.)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To simplify the expression \((3 - 1)(6 + 5)\) using the Distributive Property, first evaluate the expressions inside the parentheses: \[ (3 - 1) = 2 \quad \text{and} \quad (6 + 5) = 11. \] Now, multiply the results: \[ 2 \times 11 = 22. \] Now for the second expression \((3x - 1)(3 + 3)\): First, address the second parentheses: \[ (3 + 3) = 6. \] Then, apply the Distributive Property: \[ (3x - 1) \times 6 = 6 \cdot 3x - 6 \cdot 1 = 18x - 6. \] So, the simplified answers are: \[ (3 - 1)(6 + 5) = 22 \] \[ (3x - 1)(3 + 3) = 18x - 6. \] Thus, the final answer is \( \boxed{22} \) and \( \boxed{18x - 6} \).